The Bankers' Almanac world ranking: the top 3000 international banks ranked by total assets (England Reed Information services, 1991)
The basis of all the rankings is the size of total assets. The percentage increase or decrease in asset over the previous year is given, as is the paid-up share capital figure. The percentage change in assets is calculated in the local currency of the bank
osc 9/11/2021
Ref
Keywords: Banks and banking--Ratings and rankings